Biophilic Urbanism: Harnessing natural elements to enhance the performance of constructed assets - Reeve, A.; Hargroves, Charlie; Desha, C.; Newman, Peter; el Baghdadi, O. (Queensland University of Technology, 2013)
Creating climate resilient, low-carbon urban environments and assets is a policy goal of many governments and city planners today, and an important issue for constructed asset owners. Stakeholders and decision makers in urban environments are also responding to growing evidence that cities need to increase their densities to reduce their footprint in the face of growing urban populations. Meanwhile, research is highlighting the importance of balancing such density with urban nature, to provide a range of health and wellbeing benefits to residents as well as to mitigate the environmental and economic impacts of heavily built up, impervious urban areas. Concurrently achieving this suite of objectives requires the coordination and cooperation of multiple stakeholder groups, with urban development and investment increasingly involving many private and public actors. Strategies are needed that can provide ‘win-win’ outcomes to benefit these multiple stakeholders, and provide immediate benefits while also addressing the emerging challenges of climate change, resource shortages and urban population growth. Within this context, ‘biophilic urbanism’ is emerging as an important design principle for buildings and urban areas. Through the use of a suite of natural design elements, biophilic urbanism has the potential to address multiple pressures related to climate change, increasing urban populations, finite resources and human’s inherent need for contact with nature.The principle directs the creation of urban environments that are conducive to life, delivering a range of benefits to stakeholders including building owners, occupiers and the surrounding community. This paper introduces the principle of biophilic urbanism and discusses opportunities for improved building occupant experience and performance of constructed assets, as well as addressing other sustainability objectives including climate change mitigation and adaptation. The paper presents an emerging process for considering biophilic design opportunities at different scales and highlights implications for the built environment industry. This process draws on findings of a study of leading cities internationally and learnings related to economic and policy considerations. This included literature review, two stakeholder workshops, and extensive industry consultation, funded by the Sustainable Built Environment National Research Centre through core project partners Western Australian Department of Finance, Parsons Brinckerhoff, Townsville City Council City Solar Program, Green Roofs Australasia, and PlantUp.